The influence of investor identity and contract terms on firm value: Evidence from PIPEs - Billett, Matthew T.; Elkamhi, Redouane; Floros, Ioannis V. (Journal of Financial Intermediation, 2015)
Financial relationships can alleviate the adverse effects of asymmetric information and agency costs on outside stakeholders. We examine announcement returns to PIPE transactions, conditional on the contract terms and identity of the investor. We find that the influence of contract terms on announcement returns depends on investor identity. For PIPEs with hedge fund investors, the inclusion of control terms associates with much larger announcement returns. In contrast, announcement returns for PIPEs, involving strategic investors, are less dependent on the existence of control terms. We find the opposite for liquidity terms. Namely, announcement returns are dramatically different for strategic investors with and without liquidity terms, while inclusion of liquidity terms is less influential when PIPEs involve hedge funds. Our findings suggest that investor identity and contract terms jointly influence market reactions to PIPEs.